Library charges: an investigation into the feasibility of introducing user fees at the Kabarnet District library in Kenya - Chebon, Philemon Kiprop (Library and Information Studies Centre (LISC), 2024)
This study investigates the feasibility of introducing user fees at the Kabarnet District Library a branch of the Kenya National Library Services (KNLS). The study consisted of two main approaches: the first was a conceptual review of the literature in the field and the second was an empirical study. The purpose of the literature review was to give an overview of the literature in the field. It was during the 1980s that the subject was thoroughly investigated and this review to a large extent focuses on that period. The review begins by discussing the topic from the point of view of the developed world, and then proceeds to the situation in Africa with special reference to Kenya. The second approach involved an empirical study at the Kabarnet District Library, which was conducted between January and February 2000. The study was based on a survey study of 74 library patrons and 27 staff members. In addition interviews were conducted in 14 institutions served by the mobile library. Other stakeholders were also interviewed, which include the co-ordinators of local NGO's, primary school teachers and the Kabarnet Town Clerk. Questionnaires and interviews were the primary data collection tools. The questionnaires contained both open and closed ended questions. Both primary and secondary sources were used to collect the data required for the study, viz. directly from respondents and from government and KNLS publications. The survey reports the users' views regarding the library services, their opinions, willingness to pay user fees and the likely effects of user fees. The study also examined whether it is cost effective to introduce user fees taking into consideration the financial implications and staff time needed to implement the scheme. The study further examines the role of the mobile library services and specifically its funding implications, i.e. whether it is economical to run and the feasibility of introducing user fees to reduce the running costs. The data collected was analysed using STATA software. The data was evaluated and conclusions drawn. The results show that the services offered by the Kabamet District Library are inadequate, largely due to substantially inadequate funding and that there is an urgent need to inject more money to improve the service. However, it is apparent that although the users are willing to share costs, the introduction of user fees would not offer a solution since the amount likely to be generated will be minimal as the patrons are willing to pay only an insignificant amount. The study has shown that user fees will negatively affect those who are in the most need of the service and who are also the least able to pay. These include students and the unemployed. One of the main recommendations of the study is that alternative income generating activities be implemented to generate the much needed funds. Such initiatives would include establishing a bindery unit, a cafeteria, a video library and the letting of halls. A further recommendation is that a levy should be introduced on services which have direct financial implications on the library service operation e.g. the mobile library, ILL, and postal services. The study concludes with recommendations for further investigations which could encompass the whole KNLS network. Proposals are outlined which could be used as a basis for further research.